First report of Babesia divergens infection in an HIV patient. (April 2015) - González, Luis M.; Castro, Emma; Lobo, Cheryl A.; Richart, Alberto; Ramiro, Raquel; González-Camacho, Fernando; Luque, Daniel; Velasco, Aurelio C.; Montero, Estrella
Highlights: The first case of babesiosis caused by Babesia divergens in a patient with HIV. Transfusion transmission and natural routes of infection were evaluated. Babesia specific antibodies were detected by IFA/WesternBlot /ELISA in the patient and in one donor. The patient's humoral status showed exposure to the parasite before any transfusion. Sensitive tests are needed to fully recognize the status of babesiosis in Europe. Abstract: Human babesiosis is a zoonosis primarily transmitted through Ixodes ticks and alternatively by routes such as blood transfusions from asymptomatic donors. We report the first case of human babesiosis caused by Babesia divergens in a patient with HIV. This study also focuses on elucidating the possible transmission route of infection in this patient, who received numerous blood transfusions but showed patent symptoms only after splenectomy. A battery of detection tools along with a novel Western-Blot Assay and Enzyme Linked Immunosorbent Assay using the major surface protein of B. divergens (Bd37) as a target were used to evaluate the presence of B. divergens or antibodies against the parasite in samples from the patient and the blood donors involved in this case. A retrospective study of the humoral status against the parasite revealed B. divergens IgG antibodies in one of the implicated donors, but also showed that the patient had been already exposed to the parasite before any transfusion. Thus, this analysis of natural and transfusion transmission routes suggests a pre-existing subclinical babesiosis in the patient.